Experimental Investigation of Zadoff-Chu Matrix Precoding for Visible Light Communication System with OFDM Modulation - Xinyue Guo; Yang Guo; Shuangshuang Li (Advances in Condensed Matter Physics)
Light-emitting diode- (LED-) based visible light communication (VLC) has become a potential candidate for next generation high-speed indoor wireless communication. Due to the limited modulation bandwidth of the LED, orthogonal frequency division multiplexing (OFDM) modulation is particularly preferred in the VLC system to overcome the ISI, which suffers from the high peak-to-average power ratio (PAPR) and leads to severe performance loss. In this paper, we propose and experimentally demonstrate a novel Zadoff-Chu matrix (ZCM) precoding scheme, which can not only reduce the PAPR, but also provide uniform signal-to-noise ratio (SNR) profile. The theoretical analysis and simulation show that the proposed scheme achieves better PAPR performance compared with the traditional precoding schemes. The experimental demonstration further validates the bit error rate (BER) performance improvement, where the measured BERs are all below the 7% pre-forward error correction (pre-FEC) limit of 3.8 × 10−3 when the transmitted data rate is 50 Mb/s.